Application and Practice of Pancasila in Environmental Preservation - Hasna, Salsabila (Jurnal Scientia Indonesia, 2016)
Pancasila in environmental sustainability discusses how to preserve the environment and the laws contained in the Act that are in accordance with the practice of Pancasila. In Indonesia alone there are many problems that occur especially regarding environmental pollution and environmental destruction which causes inconvenience to some people in the environment. Legally regulated about environmental management. In every precept in the Pancasila, various applications and practices of the community have been regulated in addressing this already polluted environment. Indonesian citizens in particular, must be able to carry out the mandate that the environment is a shared environment, meaning that they must participate in preserving the environment so that it is not polluted by undesirable things. The most needed thing in carrying out this mandate is one of them is public awareness in preserving the environment. Awareness is very important because it can change the perspective of one human being with another. Various efforts have been made by the government and citizens to preserve the environment and manage the environment efficiently.